Influence of fibre configuration on the mechanical behaviour of standard test specimens and full-scale beams made of flowable FRC. (15th May 2016) - Sarmiento, E.V.; Geiker, M.R.; Kanstad, T.
Highlights: Computed Tomography was used to study local variations in fibre orientation and distribution. Full-scale casting induced fibre inhomogeneities that were not reflected in test specimens. Load-carrying capacity and crack pattern strongly depended on the fibre configuration. Small-scale notched specimens evidenced limitations for predicting structural performance. Abstract: A large and unpredictable variation in the performance of flowable fibre-reinforced concrete limits its use in structural applications. The experimental programme presented in this paper aimed at evaluating the influence of fibre configuration (i.e. orientation and distribution) on the flexural behaviour of full-scale structural beams. The investigation focused on flowable fibre-reinforced concrete with high ductility provided by 2 vol.% steel fibres with a length of 60 mm. For this high fibre dosage, rigid interactions between fibres during casting can be expected. Computed Tomography scanning of the fibre concrete revealed large variations in fibre orientation and volume content. These inhomogeneities caused differences in the mechanical behaviour. The activation of cracks in locally weak areas proved to be decisive for the crack propagation and the load-carrying capacity of the beams. Notched specimens were assessed with three-point bending and uniaxial tension tests. The inhomogeneous configuration of the fibres predetermined the location of cracks in the full-scale structural beams and was identified as the main cause of the overestimation of structural behaviour using standard test methods.